Kuby Immunology - Owen, Judith A Punt, Jenni (W.H.Freeman and Company, 2013)
Presenting current concepts in an experimental context, Kuby Immunology has been thoroughly updated to include a new chapter on innate immunity, a capstone chapter on immune responses in time and space, and many new focus boxes drawing attention to exciting clinical, evolutionary and experimental connections that help bring the material to life.